Misaligned Meaning: Couples’ Work-Orientation Incongruence and Their Work Outcomes - Jiang, Winnie Y.; Wrzesniewski, Amy (Organization Science, 2022)
This research investigates the relationship between couples’ work-orientation incongruence—the degree to which romantic partners view the meaning of their own work differently—and their ability to succeed in making job transitions and experiencing satisfaction with the jobs they hold. We use a social information-processing approach to develop arguments that romantic partners serve as powerful social referents in the domain of work. By cueing social information regarding the salience and value of different aspects of work, partners with incongruent work orientations can complicate each other’s evaluation of their own jobs and the jobs they seek. In a longitudinal study of couples in which one partner is searching for work, we find that greater incongruence in couples’ calling orientations toward work relates to lower reemployment probability, a relationship that is mediated by an increased feeling of uncertainty about the future experienced by job seekers in such couples. Calling-orientation incongruence also relates to lower job satisfaction for employed partners over time. We contribute to the burgeoning literature on the role romantic partners play in shaping work outcomes by examining the effect of romantic partners’ perception of the meaning of work, offering empirical evidence of the ways in which romantic partners influence key work and organizational outcomes. Our research also contributes to the meaning of work literature by demonstrating how work-orientation incongruence at the dyadic level matters for individual work attitudes and success in making job transitions.